TANGGAPAN ANAK SD TENTANG ANALISIS ISI RUBRIK ANAK MINGGUAN WASPADA - Rusni UMA (Universitas Medan Area, 2016)
This research aim to describe Rainbow Child rubric of Waspada weekly newspaper and to describe comments of Kartika elementary school student at Medan city. Rainbow Child rubric of Waspada presented in the form of items and theme including news, fiction stourry, quiz, and also child consignment like picture result of child masterpiece, namely doodle and cartoon. Population from Rainbow Child rubric of Waspada weekly newspaper is Rainbow take 12 published edition that assumed have adequete and deputized. Researcher use content analysis to see how theme and items at Rainbow Child rubric of Waspada. Researcher use Holsti’s formula as base guidance to measure reliability in categorizing items and theme which published at Rainbow Child rubric of Waspada. Result of decoding and measurement from researcher as decoder 1 and decoder 2, please depict that items also theme presented in Rainbow Child rubric of Waspada as elementary school student reading material can reach adequate relibility between 0,90 to 1 or 90 to 100%. To measure effect from appearance Rainbow Child of Waspada, researcher use survey by enquette to know elemntary school student comments. Population taken away from Kartika elementaryu school student which consisting of Kartika I-1 and I-2 elementary school rstudent. Taken sample around 33 elementary school student at class 5 and clasrs 6. Researcher took elementary school student at class 5 and class 6 as sampel. Result of survey by enqutte describe that items and theme from quiz and news get comments which are positive compared to fiction story, child consignment like picture result of child masterpiece, namely doodle and cartoon. Though reading materials which presented in Rainbow Child rubric of Waspada is aim to Kartika elementary school student which on age of elementary school period, but Kartika elementary schtool student which on age of elementary school period, but Kartika elemtary school students getting it from television and comic also.